Divergence and Convergence of Automobile Fuel Economy Regulations - Iguchi, Masahiko (Springer, 2015)
This book reveals the mechanisms underlying the convergence of car fuel economy regulations in Europe, Japan and the US by drawing upon a constructivist theory of International Relations and law that focuses on business competition and environmental regulations. It offers new understanding of the topic of cars and an issue of climate change, discussing the emerging phenomenon of convergence of fuel economy regulations; addressing the role of business actors in pushing for climate change action; proposing the new model of agency with and beyond states; and providing insightful case studies from Europe, Japan and the US.